The effects of cognitive training on executive functions and reading in typically-developing children with varied socioeconomic status in Brazil - Janaina Weissheimer; Renata Callipo Fujii; Juliana Geizy Marques Souza (Ilha do Desterro)
Recent findings show that children from low-socioeconomic status (SES) tend to have reduced performance on several tasks involving working memory, attention and executive control.  In addition, researchers argue for the effectiveness of training of these same cognitive skills as a way to ameliorate children’s EF skills as well as scholastic outcomes. To investigate possible training effects and to study the impact of SES on scholastic achievement in Brazilian children, we trained 61 children for 5-7 weeks and compared their performance with that of 60 age-matched peers on measures of executive functions and reading. Our results demonstrate a general effect of SES for the dependent variables. Furthermore, our findings demonstrate a positive near transfer effect on a working memory and a selective attention test and a far transfer effect on the words and pseudowords reading measure.